Continuous spinal anesthesia versus combined spinal epidural block for major orthopedic surgery: prospective randomized study - Imbelloni, Luiz Eduardo (2009)
CONTEXT AND OBJECTIVES: In major orthopedic surgery of the lower limbs, continuous spinal anesthesia (CSA) and combined spinal epidural anesthesia (CSE) are safe and reliable anesthesia methods. In this prospective randomized clinical study, the blockading properties and side effects of CSA were compared with single interspace CSE, among patients scheduled for major hip or knee surgery. DESIGN AND SETTING: Prospective clinical study conducted at the Institute for Regional Anesthesia, Hospital de Base, São José do Rio Preto. METHODS: 240 patients scheduled for hip arthroplasty, knee arthroplasty or femoral fracture treatment were randomly assigned to receive either CSA or CSE. Blockades were performed in the lateral position at the L3-L4 interspace. Puncture success, technical difficulties, paresthesia, highest level of sensory and motor blockade, need for complementary doses of local anesthetic, degree of technical difficulties, cardiocirculatory changes and postdural puncture headache (PDPH) were recorded. At the end of the surgery, the catheter was removed and cerebrospinal fluid leakage was evaluated. RESULTS: Seven patients were excluded (three CSA and four CSE). There was significantly lower incidence of paresthesia in the CSE group. The resultant sensory blockade level was significantly higher with CSE. Complete motor blockade occurred in 110 CSA patients and in 109 CSE patients. Arterial hypotension was observed significantly more often in the CSE group. PDPH was observed in two patients of each group. CONCLUSION: Our results suggest that both CSA and CSE provided good surgical conditions with low incidence of complications. The sensory blockade level and hemodynamic changes were lower with CSA. CLINICAL TRIAL REGISTRATION NUMBER: NCT00616044